2001
DOI: 10.1086/337972
|View full text |Cite
|
Sign up to set email alerts
|

The Generation of Nonthermal Particles in the Relativistic Magnetic Reconnection of Pair Plasmas

Abstract: Particle acceleration in magnetic reconnection of electron-positron plasmas is studied by using a particle-in-cell simulation. It is found that significantly large number of non-thermal particles are generated by the inductive electric fields around an X-type neutral line when the reconnection outflow velocity, which is known to be an Alfvén velocity, is of the order of the speed of light. In such a relativistic reconnection regime, we also find that electrons and positrons form a power-law-like energy distrib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
330
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(360 citation statements)
references
References 12 publications
25
330
0
5
Order By: Relevance
“…The magnetic reconnection might proceed in separate X-points but in average the process remains one-dimensional because the released energy is confined to a layer around the field reversal. Acceleration of relativistic electrons close to an X-point was considered by Romanova & Lovelace (1992); Zenitani & Hoshino (2001), Larrabee et al(2002) who found a powerlaw particle distribution with the slope β ∼ 1. Reconnection in a long current sheet at a time-scale large enough that particles pass many X-points has not been considered yet.…”
Section: Particle Acceleration By Driven Reconnectionmentioning
confidence: 99%
“…The magnetic reconnection might proceed in separate X-points but in average the process remains one-dimensional because the released energy is confined to a layer around the field reversal. Acceleration of relativistic electrons close to an X-point was considered by Romanova & Lovelace (1992); Zenitani & Hoshino (2001), Larrabee et al(2002) who found a powerlaw particle distribution with the slope β ∼ 1. Reconnection in a long current sheet at a time-scale large enough that particles pass many X-points has not been considered yet.…”
Section: Particle Acceleration By Driven Reconnectionmentioning
confidence: 99%
“…But to what extent this kinetic energy is distributed between the bulk flow velocity of the outflows, their thermal energy, and a possible high-energy tail, as well as the properties of the high-energy tail, are open questions. This mechanism is inefficient for non-relativistic reconnection because the acceleration zone is too short (along the outflow direction) (Drake et al 2010;Kowal et al 2011;Drury 2012) and affects too few particles, but is efficient under relativistic conditions where the larger reconnection electric field creates a wider acceleration zone (Zenitani & Hoshino 2001. It has indeed been found, with PIC simulations of relativistic reconnection, that power-law tails are produced through particle acceleration by E rec .…”
Section: Introductionmentioning
confidence: 99%
“…It has indeed been found, with PIC simulations of relativistic reconnection, that power-law tails are produced through particle acceleration by E rec . Several indexes are found, for example, measuring the index p as dn e /dγ ∝ γ −p and retaining only relativistic PIC simulations that all concern pair plasmas: Zenitani & Hoshino (2001) (2D): p = 1 for particles around the X-point and for the total spectra; Zenitani & Hoshino (2007) (2D): p = 3.2 and 2.4 at late times; Jaroschek et al (2004) (2D): p = 1 for particles around the X-point, modified to p = 3 by island acceleration in the whole domain; Jaroschek et al (2008) (2D, two colliding current sheets): power law; Sironi & Spitkovsky (2011a) (2D, stripped pulsar wind): p = 1.4 after the shock; Cerutti et al (2013) (2D): p = 3.8; Sironi & Spitkovsky (2014) (2D without guide field): p = 4, 3, 2, 1.5 for inflow magnetizations σ = 1, 3, 10, 30, 50 and a saturation above 50, and p = 2.3 in 3D with σ = 10. On the other hand, Kagan et al (2013) (3D) find a high-energy tail but interpret it as not having a power-law shape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…case of an electron-positron plasma, which has been most widely explored in the literature, both in 2D (Zenitani and Hoshino 2001Zenitani and Hesse 2008;Jaroschek et al 2004Jaroschek et al , 2008Bessho and Bhattacharjee 2005, 2012Daughton and Karimabadi 2007;Lyubarsky and Liverts 2008;Cerutti et al 2012bCerutti et al , 2013Werner et al 2014) and in 3D (Zenitani and Hoshino 2008;Yin et al 2008;Liu et al 2011;Spitkovsky 2011a, 2012;Kagan et al 2013;Cerutti et al 2014b;Sironi and Spitkovsky 2014;Guo et al 2014). The physics of relativistic electron-proton reconnection, yet still at an early stage of investigation, shows remarkable similarities with electronpositron reconnection (Melzani et al 2014).…”
Section: Structure Of the Reconnection Layermentioning
confidence: 99%